A Conceptual Analysis: A Model for Developing Village Entrepreneurship Through the Mudharabah Contract - Abdul Wakil; Evrita Putri Azzahroh; Rizka Amaliyah Maghfiroh; Ciptia Khoirulina Sanawati; Nur Fazillah Milawati; Baiq Ismiati (Al-Hisbah Jurnal Ekonomi Syariah, 2025)
This study aims to formulate a conceptual model of village entrepreneurship development based on the mudharabah contract within the perspective of Islamic economics. The research method employs a descriptive qualitative approach through systematic literature review and conceptual analysis using the framework of maqashid al-shariah. Thematic analysis was conducted on literature discussing the practice of mudharabah, village-based micro, small, and medium enterprises UMKM, and economic digitalization, resulting in a synthesis of the role of this contract in rural economic development. The findings reveal that mudharabah functions as a multifunctional instrument: first, providing more equitable access to capital through profit-sharing schemes; second, strengthening social solidarity through transparency and trustworthiness (amanah); third, fostering spiritual motivation with an orientation toward blessings (barakah); fourth, building digital trust for village products in online marketplaces; and fifth, enhancing community resilience against business risks.